2007
DOI: 10.1051/0004-6361:20066193
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution X-ray spectroscopy of T Tauri stars in the Taurus-Auriga complex

Abstract: Context. Differences have been reported between the X-ray emission of accreting and non-accreting stars. Some observations have suggested that accretion shocks could be responsible for part of the X-ray emission in classical T Tauri stars (CTTS). Aims. We present high-resolution X-ray spectroscopy for nine pre-main sequence stars in order to test the proposed spectroscopic differences between accreting and non-accreting pre-main sequence stars. Methods. We used X-ray spectroscopy from the XMM-Newton Reflection… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
157
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(176 citation statements)
references
References 87 publications
(199 reference statements)
19
157
0
Order By: Relevance
“…The important result is that the model EMD has a pronounced peak at T ∼ 3 MK, which is exactly the feature that we observe in MP Mus and TW Hya, while no cool peak is present in the EMD of the WTTS TWA 5. The cool peak that we found in the EMD of the two CTTS TW Hya and MP Mus explains, in terms of EMD, the soft flux excess observed in the X-ray spectra of CTTS in the XEST survey Telleschi et al 2007). …”
Section: Soft X-rays From Shock-heated Plasma: Emdsupporting
confidence: 58%
See 1 more Smart Citation
“…The important result is that the model EMD has a pronounced peak at T ∼ 3 MK, which is exactly the feature that we observe in MP Mus and TW Hya, while no cool peak is present in the EMD of the WTTS TWA 5. The cool peak that we found in the EMD of the two CTTS TW Hya and MP Mus explains, in terms of EMD, the soft flux excess observed in the X-ray spectra of CTTS in the XEST survey Telleschi et al 2007). …”
Section: Soft X-rays From Shock-heated Plasma: Emdsupporting
confidence: 58%
“…The idea of accretion-driven X-rays from CTTS is superficially supported by a soft X-ray excess found in highresolution X-ray spectra of CTTS with respect to similar spectra of WTTS by Telleschi et al (2007) and . However, and noted that this soft X-ray excess is significantly lower than that predicted by simple models of X-ray emission from accretion shocks.…”
Section: Article Published By Edp Sciencesmentioning
confidence: 93%
“…1) derived with the PINTofALE spectral code (Kashyap & Drake 2000) with the APED V1.3 atomic line database (Smith et al 2001), assuming the same metal abundances as before (as deduced from X-ray observations of CTTSs; Telleschi et al 2007). We use the ideal gas law, P = (γ − 1)ρ .…”
Section: Mhd Modelingmentioning
confidence: 99%
“…Preibisch et al 2005;Telleschi et al 2007b). Drake et al (2009) suggested that it is not the accretion of the CTTS that causes their low luminosity but rather, the low luminosity that allows the disk to approach the star more closely, i.e., weaker emitters to accrete and become CTTS.…”
Section: Varying Absorption?mentioning
confidence: 99%